Longevity and ageing: appraising the evolutionary consequences of growing old. - Bonsall, M (2006)
Senescence or ageing is an increase in mortality and/or decline in fertility with increasing age. Evolutionary theories predict that ageing or longevity evolves in response to patterns of extrinsic mortality or intrinsic damage. If ageing is viewed as the outcome of the processes of behaviour, growth and reproduction then it should be possible to predict mortality rate. Recent developments have shown that it is now possible to integrate these ecological and physiological processes and predict the shape of mortality trajectories. By drawing on the key exciting developments in the cellular, physiological and ecological process of longevity the evolutionary consequences of ageing are reviewed. In presenting these ideas an evolutionary demographic framework is used to argue how trade-offs in life-history strategies are important in the maintenance of variation in longevity within and between species. Evolutionary processes associated with longevity have an important role in explaining levels of biological diversity and speciation. In particular, the effects of life-history trait trade-offs in maintaining and promoting species diversity are explored. Such trade-offs can alleviate the effects of intense competition between species and promote species coexistence and diversification. These results have important implications for understanding a number of core ecological processes such as how species are divided among niches, how closely related species co-occur and the rules by which species assemble into food-webs. Theoretical work reveals that the proximate physiological processes are as important as the ecological factors in explaining the variation in the evolution of longevity. Possible future research challenges integrating work on the evolution and mechanisms of growing old are briefly discussed.